Beispiel Nr: 19
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +1 y =2\\ 3 x +3 y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 1 x +1 y =2\\ II \qquad 3 x +3 y = 3 \\ I \qquad 1 x +1 y =2 \qquad / \cdot3\\ II \qquad 3 x +3 y = 3 \qquad / \cdot\left(-1\right)\\ I \qquad 3 x +3 y =6\\ II \qquad -3 x -3 y = -3 \\ \text{I + II}\\ I \qquad 3 x -3 x+3 y -3 y =6 -3\\ \\ L=\{\}\end{array} & \begin{array}{l} \\I \qquad 1 x +1 y =2\\ II \qquad 3 x +3 y = 3 \\ I \qquad 1 x +1 y =2 \qquad / \cdot3\\ II \qquad 3 x +3 y = 3 \qquad / \cdot\left(-1\right)\\ I \qquad 3 x +3 y =6\\ II \qquad -3 x -3 y = -3 \\ \text{I + II}\\ I \qquad 3 x -3 x+3 y -3 y =6 -3\\ \\ L=\{\}\end{array} \end{array} $